A nano-micro dual-scale particulate-reinforced copper matrix composite with high strength, high electrical conductivity and superior wear resistance. Issue 54 (31st August 2018) - Zou, Cunlei; Chen, Zongning; Guo, Enyu; Kang, Huijun; Fan, Guohua; Wang, Wei; Li, Rengeng; Zhang, Siruo; Wang, Tongmin
Abstract : A nano Cu5 Zr and micro ZrB2 dual-scale particulate-reinforced copper matrix composite is prepared by in situ synthesis and heat treatment, which has high strength, high electrical conductivity and superior wear resistance. Abstract : Due to the contradiction between mechanical properties and electrical conductivity, it is not easy to fabricate materials with both high strength and good wear resistance with favourable electrical conductivity for the application of electrical materials. In addition, strength and wear resistance do not always present a uniform growth trend at the same time. Herein, a novel copper matrix composite reinforced by in situ synthesized ZrB2 microparticles and nano Cu5 Zr precipitates is successfully prepared by a casting method and sequential heat treatments. The Cu/dual-scale particulate composite possesses a desired trade-off of strength, electrical conductivity and wear resistance. ZrB2 microparticles form from Zr and B elements in copper melts, and nanoscale Cu5 Zr precipitates form in the matrix after solid solution and aging treatments. The ZrB2 microparticles, nano Cu5 Zr precipitates, and well-bonded interfaces contribute to a high tensile strength of 591 MPa and superior wear resistance, with a relative electrical conductivity of 83.7% International Annealed Copper Standard.